PENERAPAN MODEL PEMBELAJARAN SELF-DIRECTED LEARNING UNTUK MENINGKATKAN MOTIVASI BELAJAR EKONOMI SISWA KELAS XI MA HASANAH PEKANBARU - Lia Novia; Suarman Suarman; Sumarno Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to improve economic learning motivation of class XI students of Pekanbaru MA Hasanah. This research was conducted at Pekanbaru Hasanah MA on economic subjects. This research was conducted in May-October 2018. This study uses a quantitative approach. The population of this study was 16 students, the population type was sampled. The data collection techniques used were questionnaires, motivation before and after learning. The data analysis technique used was the t test. The results showed that the application of the SDL (Self D irected Leraning) model had differences between motivation before and after using SDL, ie motivation after higher than before using the SDL model. Thus the SDL model can be used as an alternative for economic learning because this model can increase motivation before and after learning. Student learning motivation from the average before 74,562 after 88,187.Key Words: SDL (Self D irected Leraning) Model, Learning Motivation